Microsoft Visual C++ MFC library reference (Microsoft Press, 1997)
Visual C++ is the world's premiere C/C++ development environment. Detailed information is presented here about the MFC classes, their member functions and data members, global variables and functions, macros, styles, structures, callback functions, and hierarchy charts.